OP I – 6 Outdoor air pollution, greenspace and incidence of adhd in saxony: a semi-individual cohort study. (18th March 2018) - Markevych, Iana; Tesch, Falko; Datzmann, Thomas; Romanos, Marcel; Schmitt, Jochen; Heinrich, Joachim
Abstract : Background/aim: Attention deficit hyperactivity disorder (ADHD) is a frequent mental disorder with onset in childhood and largely unknown aetiology. It has been speculated that apart of genetic and lifestyle factors, the environment could also contribute to the ADHD onset but evidence is very scarce. We investigated whether outdoor air pollution and greenspace affect ADHD incidence in children residing in Saxony. Methods: 66 823 children from the population-based statutory health insurance company AOK PLUS born between 2000 and 2004 were followed until 2014. We considered any child with at least one ICD-10-GM F90 diagnosis ever by a child/adolescent psychiatrist, neuropaediatrician or psychotherapist an ADHD case. Children's home addresses were known up to their four-digit postal code area. Population-weighted mean values of particulate matter with diameter of less than 10 µm (PM10), nitrogen dioxide (NO2) and MODIS Normalised Difference Vegetation Index (NDVI) were calculated for 186 postal code areas. Associations with each exposure were assessed by two-level adjusted Poisson regression models. Results: 2044 children (3.06%) were diagnosed with ADHD within the observation period. Pearson correlation coefficients between PM10, NO2 and NDVI were ≥|0.80|. An increase of PM10 and NO2 by 10 µg/m³ raised the relative risk of ADHD by a factor of 1.97 [95% CI: 1.35–2.86] and 1.32 [1.10–1.58], respectively. 0.1-unit increase in NDVI decreased the relative risk of ADHD by a factor of 0.82 [0.68–0.98]. Better access to child psychiatrists was the most important confounder that increased ADHD risk across all models. Conclusion: Our results provide some evidence that environmental factors might affect ADHD. Future studies with more detailed address information and better control for confounding, in particular for socioeconomic status and parental psychopathology, should clarify whether the observed associations are true.